2023
DOI: 10.1186/s12887-023-03892-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the ability of HOMA-IR, VAI, and TyG indexes to predict metabolic syndrome in children with obesity: a cross-sectional study

Abstract: Background The increasing trend in childhood obesity needs to be closely monitored and intervened due to long-term health issues such as metabolic syndrome, cardiovascular diseases, hypertension, and type 2 diabetes. We aimed to determine and compare the cut-off values for the visceral adiposity index (VAI), triglyceride-glucose index (TyG), and HOMA-IR for predicting metabolic syndrome (MetS). Methods This population-based cross-sectional study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Although HOMA-IR is a recognized indicator of insulin resistance (IR) in adults, in our study HOMA-IR did not differentiate well between children with and without MAFLD. Similar conclusions about the limited diagnostic value of this indicator, especially in the pediatric population, which lacks standardized reference values, have been raised by researchers before [6,24]. However, due to limited availability and the difficulty of performing HEC, HOMA-IR is widely used for the diagnosis of IR, but it is also used as a reference in some studies to assess the utility of other indices, which may cause inaccurate results [19,25,26].…”
Section: Discussionmentioning
confidence: 68%
“…Although HOMA-IR is a recognized indicator of insulin resistance (IR) in adults, in our study HOMA-IR did not differentiate well between children with and without MAFLD. Similar conclusions about the limited diagnostic value of this indicator, especially in the pediatric population, which lacks standardized reference values, have been raised by researchers before [6,24]. However, due to limited availability and the difficulty of performing HEC, HOMA-IR is widely used for the diagnosis of IR, but it is also used as a reference in some studies to assess the utility of other indices, which may cause inaccurate results [19,25,26].…”
Section: Discussionmentioning
confidence: 68%
“…Obesity, a global health concern, is intrinsically linked to a variety of health hazards, such as glucose intolerance [15], insulin resistance [16], and metabolic abnormalities [17], all of which can precipitate the onset, progression, and prognosis of cerebrovascular disease [18][19][20]. The TyG index, in conjunction with obesity indices, has been identified to be closely related to insulin resistance [21,22], metabolic syndrome [23], uric acid [24], diabetes mellitus [25], and fatty liver [26]. Some studies have even suggested that the combination of the TyG index with adiposity indices may outperform the TyG index alone in assessing stroke risk [27].…”
Section: Main Text Introductionmentioning
confidence: 99%